FORMING OF INVESTMENT RESOURCE OF STRUCTURAL MODERNIZATION OF NATIONAL ECONOMY AS FACTOR OF RENEWAL IN A POST-WAR PERIOD - Sakun , O.S.; Shchur, R. I.; Matskiv, V.V.; Bilyi, M.M. (The actual problems of regional economy development, 2023)
The article is devoted the analysis of value of forming of investment resource of structural modernization of economy for post-war renewal of Ukraine. In investigation of military operations through Russian aggression a national economy suffers today from crisis displays and deep regional disproportion which is a substantial obstacle on the way of economic renewal and getting up in a post-war period. The effective model of intensive development of national economy is dynamic growth of GDP, which would enable to provide constantly growings public necessities at maximally ideal terms. It predetermines the necessity of observance of permanent rates of economic development in the conditions of complete application of exhausted of production resources, above all things, labour, providing of stability of prices and strong position of domestic economy within the limits of world market. In the conditions of post-war renewal the question is also about renewal of infrastructure, but already after on principle new modern standards, that needs innovative approach. The purpose of the article is opening teoretiko-methodological principles of forming of investment resource and finding out of practical aspects of his value for structural modernization of economy of Ukraine in the conditions of post-war renewal. Coming from financial exhaustion of country by war and insufficiency of budgetary resources, important value, is acquired by bringing in of investments. And taking into account a necessity not simply renewal, but also innovative re-erecting, leading role the investment resource of structural modernization of economy acquires in such processes. It can be defined, as a dynamic system of selection and combination informatively legal, financial, intellectual and material and technical component, which will be used for renewal and development of the economic system of country in a post-war period. Forming of investment resource of structural modernization of national economy through offered on-line platform is an important task on the way of post-war renewal of Ukraine which acquires the actuality already on the modern stage. Taking into account, forecast level of charges and necessity of the innovative going near the process of renewal of Ukraine, an investment resource acquires a key value for the financial providing of the put tasks.